Primary Cough Headache Associated with Jugular Insufficiency: Report of Two Cases - Zhen, Felipe; Yamaguto, Guilherme E.; Yamaguto, Thais T.; Bochnia Küster, João G.; Piovesan, Elcio J. (International Journal of Medical Students, 2022)
Background: Insufficiency of the internal jugular valve is a scarcely found etiology in the literature for the cough headache, which can be associated with other vascular disorders. The objective of this study is to report through clinical and imaging findings the rarely described association between cough headache and jugular insufficiency. Cases: Two male patients, ages 79 and 70-year-old respectively, were evaluated with episodes of headache associated with Valsalva Maneuver. The first presented with a holocranial headache and two episodes of associated syncope after cough, while the other patient reported headaches after use of an abdominal belt, as a preventive measure to contain abdominal hernia. In both cases, the insufficiency was proved upon jugular reflux on Doppler sonography. Conclusion: Those two case reports help to broaden the discussion on the possible association between primary cough headache and insufficiency of the internal jugular vein system, although the correlation between those two pathologies is still being debated